ANSWER
The correct answer is
![-26](https://tex.z-dn.net/?f=-26)
EXPLANATION
The expression given to us is,
![\frac{5}{6}( \frac{1}{2}x+ 6)-3x](https://tex.z-dn.net/?f=%5Cfrac%7B5%7D%7B6%7D%28%20%5Cfrac%7B1%7D%7B2%7Dx%2B%206%29-3x)
We plug in
![x=12](https://tex.z-dn.net/?f=x%3D12)
. That means we substitute 12 wherever we see x to obtain,
![\frac{5}{6}( \frac{1}{2}\times 12+ 6)-3\times 12](https://tex.z-dn.net/?f=%5Cfrac%7B5%7D%7B6%7D%28%20%5Cfrac%7B1%7D%7B2%7D%5Ctimes%2012%2B%206%29-3%5Ctimes%2012)
We simplify the parenthesis first to obtain,
![=\frac{5}{6}( 6+ 6)-36](https://tex.z-dn.net/?f=%3D%5Cfrac%7B5%7D%7B6%7D%28%206%2B%206%29-36)
![=\frac{5}{6}( 12)-36](https://tex.z-dn.net/?f=%3D%5Cfrac%7B5%7D%7B6%7D%28%2012%29-36)
![=5\times 2-36](https://tex.z-dn.net/?f=%3D5%5Ctimes%202-36)
![=10-36](https://tex.z-dn.net/?f=%3D10-36)
![=-26](https://tex.z-dn.net/?f=%3D-26)
Hence the expression evaluates to
there is no graph here to answer this
Fraction with x squared plus y cubed in the numerator and 2 plus x in the denominator.
3.8
14.83
19.58
23.5
Answer:
X will be your answer be 126 and 110
Step-by-step explanation:
6x3x7=126
y=11x2x5=110
so X>Y
hope it helps!